Geomythology as a Geotourism Attraction, Case Study: The Sangkuriang Legend in The Bandung Highland and Its’ Surrounding Areas Based on Geological to Hermeneutics Interpretation - Oman Abdurahman; Denny Sukamto Kadarisman (International Journal of Geotourism Science and Development, 2022)
The Bandung Highlands and its surrounding areas (BHLs) are rich in important geodiversity and geoheritage sites because of its values. They are of knowledge value, educational value, environmental value, cultural value, economic value, and others. An important one is the value of tradition in the form of legend, in this case the Sangkuriang in the Sunda community - the majority of the population is in BHLs - even in the archipelago. All of them have made the BHLs area an important geotourism destination in West Java. Meanwhile, the development of a new sub-discipline called "geomythology" provides an opportunity to make the Sangkuriang legend important. In this paper, a study is conducted on the Sangkuring legend as a form of geomythology that is popular among the BHLs people, even throughout the West Java province. Aspects of geomythology as a branch of science in the Sangkuriang legend are dissected and related to the events of the formation of BHLs and some of the mountains that surround it, ancient Bandung Lake, and important geological outcrops in it. The results of the study found that the names and sequences of events in the Sangkuriang legend matched with the geographical names and geological history of the formation of BHLs and their environment. People often associate various natural phenomena in BHLs with these legends. This is seen from the point of view of public education in geotourism is very important. Furthermore, the legend has also been interpreted with and by hermeneutic approach where the results enrich the narrative of interpretation in geotourism (geo-interpretation) in BHLs.